The potential of a terrace-wise economy: Hygassos’ agricultural heritage in the Hellenistic Rhodian Peraia (Bozburun Peninsula) - Oğuz-Kırca, E. Deniz; Liritzis, Ioannis; Demirciler, Volkan (Journal of Greek Archaeology, 2019)
The Bozburun Peninsula (Hellenistic Rhodian Peraia, i.e the mainland possessions of ancient Rhodes) lies immediately north of the Island of Rhodes (Figure 1). It is an unspoiled (it used to be incredibly barren) territory which has remained as an area of seclusion throughout history.